Chronic-periodontitis: could it be a connived-culprit of COVID-19? - Elisetti, Nirupa (International Journal Of Community Medicine And Public Health, 2021)
Periodontitis is a multi-factorial disease resulting in the disruption of the attachment apparatus. COVID-19 has been alarming to many nations despite consistent efforts. Research has been continuously going on to curb the spread of the disease by gaining knowledge on the insights of the pathology of the disease. The current exploratory research establishes a correlation between periodontitis and COVID-19 and the impact of periodontal health in COVID affected patients. A search was performed using three data bases, PubMed, Scopus and Google Scholar published from 2019 to 2020. The keywords used for the search were COVID-19, and pathogenesis of periodontitis. The results of the search resulted in many reviews, original research, systematic reviews, case reports, etc. The critical selection of the articles especially systematic reviews was given utmost importance. Much less research has been done on the correlation of periodontitis to COVID-19. On the basis of search using the above mentioned keywords, a total of 26 articles were selected out of which only 21 articles were considered for the present exploratory review. The present review provides an insight into the pathogenic aspects of both periodontitis and COVID-19 and helps in establishing an ally which has been minimally explored to date. The pathogenesis of COVID shows a close similarity to periodontitis and henceforth a possible connection of the severity of COVID in patients suffering with chronic periodontitis. Periodontitis presents itself as a risk factor for many systemic diseases, and nevertheless, it has shown a possible similarity in the pathophysiology of COVID-19.